In vivo quantification of brain volumes in subcortical vascular dementia and Alzheimer’s disease - Pantel, Johannes; Schröder, Johannes; Essig, Marco; Jauß, Jan Marek; Boyen, Georg von; Eysenbach, Katrin; Kummer, Rüdiger von; Baudendistel, Klaus; Schad, Lothar R.; Knopp, Michael V. (Dementia and geriatric cognitive disorders, 1998)
Quantitative magnetic resonance imaging (MRI) was used to assess global and regional cerebral volumes in patients with a clinical diagnosis of subcortical vascular dementia (VD) and Alzheimer’s disease (AD). Whole brain volume, cerebrospinal fluid volume, volumes of the temporal, frontal and parietal lobes, the cerebellum and the amygdala-hippocampus complex were determined using a personal computer-based software. Seventeen patients with VD, 22 patients with AD and 13 healthy controls were included. Analysis of covariance using age as covariate demonstrated significant mean differences between controls and dementia groups with respect to all morphological parameters. However, apart from the volume of the cerebellum no significant volumetric differences were found between VD and AD. These results indicate that MRI-based volumetry allows differentiation between AD or VD from normal controls and that measurement of cerebellar volume may be of use to separate vascular and degenerative dementia. However, since the distribution of cerebral atrophy in both dementia groups is very similar, it is suggested that the atrophic changes are not specific to the underlying cause but rather reflect the selective vulnerability of neuronal structures.